المنهج العلمي للإصلاح الإقتصادي - العربيد، عدنان (جامعة تشرين, 2005)
إن تطبيق المنهج العلمي للإصلاح والتحديث في مجتمع ما ممكن فقط من خلال تحقق أبعاد علم الاقتصاد في سياق إدارة الحياة الاقتصادية لهذا المجتمع، والعكس صحيح. فتحقق أبعاد علم الاقتصاد يعني تطبيقا للمنهج العلمي للإصلاح والتحديث وتجسيدا للاستقرار الديناميكي في المجتمع. وانطلاقا من كون المنهج العلمي منهجا للتعامل مع الحقائق فقط، فإن البعد الذاتي لعلم الاقتصاد يتمثل في القياس المباشر لحقائق الحياة الاقتصادية. في حين يتمثل البعد النسبي في حرية مشاركة كل من له مصلحة في هذا القياس، انطلاقا من أن تناقض أو تنافس المصالح كفيل بتحقق الدقة والموضوعية في هذا القياس وفي تأكيد الجودة والكفاءة في صناعة المعلومات، مما ينجم عنه مدخلات مثلى تقود إلى مخرجات مثلى، وهو ما تؤكده يوما بعد يوم المزايا الكبيرة لاقتصاد المعلومات، ولدور هذا الاقتصاد في دفع عجلة التنمية ككل. ويتضح البعد الجدلي من خلال مقارنة اقتصاد السوق مع التنظيمات الاجتماعية الأخرى، فلقد استطاع اقتصاد السوق، سواء من خلال قوانينه وآليته الموضوعية، أو في سياق التدخل التنموي للحكومة في الاقتصاد أن يحاكى متطلبات الإنسان وحاجاته الحقيقية والمتمثلة في حريته، وفي قدرته على الاختيار، فاستطاع هذا الاقتصاد أن يحدد ما هو ممنوع فقط، انطلاقا من الآلية أو المنطق الذي يقول: (المسموح: كل ما هو غير ممنوع)، ولهذا وفي ظل ثقافة الممنوع أو ثقافة الاختيار هذه ستضيق باستمرار ومع مرور الوقت مساحة الممنوع لصالح المسموح، ليتعمق بالتالي التقدم يوما بعد يوم، مما يجعل من آلية هذا الاقتصاد المنهج العلمي الأمثل في حل المشكلة الاقتصادية. وإن كان كل من البعد الحركي والبعد الدوري يمثلان فلسفة ومنطق الآلية في الفكر الاقتصادي، فإن البعد الموضوعي يؤكد على أن تخصيص الموارد النادرة لاستخداماتها البديلة يفترض دوما تطبيق الحل الأمثل والوحيد في تحقيق أقصى إشباع ممكن لحاجات الإنسان، ويوضح أن طبيعة ودور آلية التسعير أو نظام الأسعار، لا تكمن فقط في تحديد مجال الحياة الاقتصادية، بل في تحريك النظام الاقتصادي ككل. وإن كان البعد الاجتماعي يتضمن طبيعة ودور الإدارة التنموية لحلقة الأجور-الأسعار في سياق كبح القوى والظواهر والنتائج غير العادلة لاقتصاد السوق، فإن البعد المعياري يتناول المعايير الموضوعية أو غير القابلة للتأويل، والتي من خلالها يمكن لعلم الاقتصاد أن يقرر ما يجب أن يكون. وبناء عليه، نلاحظ أن هذه الأبعاد مجتمعة تجسد منهجا علميا تطبيقا يحقق ويجسد ثقافة الممنوع، أو ثقافة المعيار، أو حتى ثقافة الاختيار ويؤدي، فيما لو توافرت الإرادة السياسية، إلى تحقق الأهداف الحقيقية للإصلاح والتحديث في المجتمع المعني. Adopting the scientific approach to reform and modernization in our society is possible only when the aspects of economics have their role in managing the economic system, and vice versa because this leads to dynamic stability in society. As the scientific approach deals with facts only, the subjective aspect of economics is embodied in the direct representation of the facts of the economic system. The relative aspect, on the other hand, represents freedom of participation of everyone who is involved in this representation due to the fact that contradiction achieves conciseness and objectivity. This aspect also represents proficiency in information technology which shows how the ideal input leads to the ideal output. All this is proved to be right through the great characteristics of information technology that enhances development as a whole. The argumentative aspect is embodied in comparing. market economy with other social organizations because market economy could meet man's needs represented by his freedom and his ability to choose. The economy was able to do either through its rules and objective mechanism or through the government's economic plans for development. It could identify what is banned depending on the rule, which says that the allowed is every thing that is not banned. So, the space of the banned is narrowed and thus, development will increase day by day. this makes the mechanism of the scientific approach to economics the best to solve the problem of economy. While both the dynamic and the successive aspects represent the logic of the economic system, the object assures that using rare resources as alternation needs apply on only and the best solution for achieving the best results in regard to meeting human needs. It also clarifies that the nature and the role of price fixing has to do not only with assigning limits for the economic system, but also with making the price fixing system the fundamental factor in economy. The social aspect includes the nature and the role of prices management in regard to stopping the forces and the unfair results of market economy. In addition, the standard aspect deals with the objective standard through which economics can decide what must be there. Thus, we can notice that all these aspects represent a scientific approach which embodies the culture of the banned, the culture of the standard or the culture of choice, all of which lead to the achievement of the real goals of reform and modernization in the country.
Keywords: مناهج البحث -- الفكر الإقتصادي -- الإصلاح الإقتصادي -- سوريا -- البحث العلمي